2022
DOI: 10.1113/jp283784
|View full text |Cite
|
Sign up to set email alerts
|

The ketogenic diet maintains insulin sensitivity and inhibits lipid accumulation in the liver

Abstract: support-information-section).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
(38 reference statements)
0
0
0
Order By: Relevance
“…The study found that a high-carbohydrate diet increased the expression of SREBP-1c and ChREBP, two transcription factors that promote the expression of adipogenic genes, including those for FAS, ACC and lipoprotein 1, which are essential for DNL. 4,18 DNL promoted steatosis and exacerbated oxidative stress by increasing lipid synthesis. Consistent with these findings, the present study showed that diets with different levels of carbohydrate affect hepatic lipid synthesis.…”
Section: Papermentioning
confidence: 97%
See 1 more Smart Citation
“…The study found that a high-carbohydrate diet increased the expression of SREBP-1c and ChREBP, two transcription factors that promote the expression of adipogenic genes, including those for FAS, ACC and lipoprotein 1, which are essential for DNL. 4,18 DNL promoted steatosis and exacerbated oxidative stress by increasing lipid synthesis. Consistent with these findings, the present study showed that diets with different levels of carbohydrate affect hepatic lipid synthesis.…”
Section: Papermentioning
confidence: 97%
“…Studies have shown that a high carbohydrate diet increased the expression of sterol regulatory element binding protein 1c (SREBP-1c) and carbohydrate regulatory element binding protein (ChREBP), two transcription factors crucial for de novo lipogenesis (DNL). 18 This upregulation of triacylglycerol (TG) production from carbohydrates via DNL further promotes hepatic steatosis. In contrast, the ketogenic diet (KD) has recently grown in popularity as a high-fat diet that restricts carbohydrates.…”
Section: Introductionmentioning
confidence: 99%